2019
DOI: 10.1016/j.heliyon.2019.e02710
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells alleviate hydrochloric acid-induced lung injury through suppression of inflammation, oxidative stress and apoptosis in comparison to moxifloxacin and sildenafil

Abstract: IntroductionAcute lung injury (ALI) is a severe life-threatening disease causing uncontrolled pulmonary inflammation and oxidative damage. There are still no effective therapies for this disease. The aim of this study was to evaluate the protective role of mesenchymal stem cells, moxifloxacin, sildenafil or a combination of moxifloxacin and sildenafil against hydrochloric Acid (HCl) - induced ALI.MethodsHCl or saline was injected intra-tracheally and after 2 h, moxifloxacin, sildenafil, moxifloxacin + sildenaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…This gives emphasis to the relevance of restoring antioxidant levels in the effort to safeguard the most vulnerable people from severe symptoms. In a previous study, we investigated the expression of heme oxygenase-1 (HO-1) which is induced by CoPP, and it is a key player in the cellular antioxidant system in HCl-induced lung injury leading to a decrease in inflammation and in ROS production [ 6 , 11 ]. We demonstrated that the induced lung injury caused significant reduction in the expression of HO-1 at the level of mRNA, and it was upregulated by MSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives emphasis to the relevance of restoring antioxidant levels in the effort to safeguard the most vulnerable people from severe symptoms. In a previous study, we investigated the expression of heme oxygenase-1 (HO-1) which is induced by CoPP, and it is a key player in the cellular antioxidant system in HCl-induced lung injury leading to a decrease in inflammation and in ROS production [ 6 , 11 ]. We demonstrated that the induced lung injury caused significant reduction in the expression of HO-1 at the level of mRNA, and it was upregulated by MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirate content may include particles of food, gastric acid (HCl; hydrochloric acid), blood, or bacteria. Among these contents, HCl has the greatest influence on the lung injury [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MSC treatment group had a higher level of GSH, SOD, and a lower level of MDA when compared with the control group. El-Metwaly et al [ 45 ] found that MSCs increase GSH levels and reduce MDA levels in lung tissue of rats subjected to acute lung injury. Li et al [ 46 ] reported that MSCs can restore the levels of GSH and MDA in rats with chronic alcoholism, and its effects on repairing sciatic nerve were obvious.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs treatment group got a higher level of GSH, SOD, and a lower level of MDA when compared with control group. El-Metwaly et al [40] found that MSCs can increase the GSH level and reduce the MDA level in lung tissue of acute lung injury rats. Zhang et al [41] reported that MSC effectively reduced the level of MDA, and increased SOD in the lung tissue of acute lung injury rats.…”
Section: Discussionmentioning
confidence: 99%